Concentration in Asia's cross-border banking determinants and impacts - Ana Kristel Lapid; Rogelio Mercado; Peter Rosenkranz (Asian Development Bank (ADB), 2021)
Cross-border bank positions in Asia and the Pacific remain highly concentrated to few counterparties, exposing the region to financial risks and policy spillovers. Consequently, assessing the determinants and impacts of the region's cross-border banking concentration is relevant to the design of appropriate policies for promoting financial development and safeguarding financial stability. To this end, we construct cross-border bank concentration measures for 47 economies in Asia and the Pacific from 2000 to 2019. The results show that higher openness of capital account and trade, as well as better per capita income, are significantly associated with lower cross-border bank concentration. Moreover, elevated cross-border bank concentration tends to lower domestic credit growth and nonperforming loans. We find no impact on bank profitability for the region.
Keywords: E44; F36; G21; O16; 330; Asia and the Pacific; bank profitability; credit growth; cross-border bank concentration; cross-border bank exposures; nonperforming loans